Theoretical and Methodological Implications in Developing Teamwork Quality and Sustainable Culture at Top Management Level: A Literature Review - Patricia, Mia Christy; Fitriyani, Sarah (Journal of Economic and Leadership, 2024)
This qualitative literature review explores the theoretical and methodological implications of developing team quality and sustainable culture at the top management level. The study highlights the importance of structured methodologies to enhance the capabilities of top management teams (TMTs) for achieving real teamwork and fostering a sustainable quality culture. Key findings emphasize the significance of a systemic view, emotional commitment, and continuous improvement as critical elements for success. Additionally, a strong organizational culture mediates the relationship between perceived ethics and organizational performance. While providing valuable insights, this review acknowledges limitations, such as reliance on existing literature and potential generalization issues across different organizational contexts. Future research should include empirical studies to validate these findings and explore additional factors influencing team quality and sustainable culture development at the top management level.